SYNTHESIS AND BIOLOGICAL ACTIVITIES OF ACETAMINOPHEN AND IBUPROFEN METAL COMPLEXES OR DERIVATIVES: A REVIEW - Hamdan, Azni Izwati; Sukmana, Dike Dandari; Nordin, Norsyafikah Asyilla (Malaysian Journal of Science, 2024)
We reviewed scientific literature on the synthesis of acetaminophen and ibuprofen, as well as their derivatives and biological properties. The synthesis of acetaminophen involves the acetylation of 4-aminophenol and acetic anhydride, while ibuprofen is synthesised by reacting isobutyl benzene and acetic anhydride in four continuous reaction stages, which are Friedel-Crafts acylation, carbonyl reduction, chloride substitution, and Grignard reaction. To obtain their derivatives, modifications have been made either by complexing the main structure of the drug compound with metal elements or adding certain desired moieties, such as thiourea, amide, ammonium, halogen, silicon, and 1,3,4-oxadiazole. Ibuprofen and acetaminophen have been recognised as effective painkillers and anti-inflammatories. Recently, their derivatives have been implicated in a variety of biological effects. The biological activities of acetaminophen and ibuprofen derivatives have been reported to exhibit urease inhibition and inflammatory inhibition, as well as inhibit the proliferation of breast cancer cells MCF-7. Overall, this review article describes the synthesis of acetaminophen and ibuprofen derivatives, complete with their biological activities such as antimicrobial, antifungal, anti-inflammatory, urease inhibitors, and anticancer.